Efektivitas Terapi Yoga Untuk Dismenore Primer Pada Siswa SMA - Asta Adyani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to analyze the effectiveness of yoga therapy for primary desminore in high school studentsMethods: This research is quantitative with a quasi-experiment design, approaching the design of non-equivalent control group design researchers. The pre-post test was conducted for the intervention group and control group respondents. The data obtained were then analyzed using the Mann-Whitney test using SPSS.Results:   The study found a decrease in the intensity of dysmenorrhea pain in the experimental group after given yoga (p-value 0,000 < α 0,05) Conclusion: This study recommends that yoga be used for young women, especially women with dysmenorrhea, to reduce the intensity of pain dysmenorrhoea